Profile of Drug-Resistant Tuberculosis Patients at Rumah Sakit Universitas Indonesia Depok Period October 2024 - Suci Rizki Dumiarsih; Santi Purna Sari; Retnosari Andrajati; Diah Handayani (Green Publisher Indonesia, 2025)
Indonesia has been one of the three countries in Asia that contributes to the highest case of Tuberculosis (TB) in the world. Tuberculosis itself counted as the top ten cause of death globally. Two of the challenges in controlling TB cases are the occurrence of drug-resistance strain and patients’ adherence. Drug-resistant TB has to be treated with the second line drugs of TB with higher risk of adverse events. Linezolid as one of the suggested drugs by WHO in the treatment may increase patients’ risk of cytopenia events. This study was conducted to represent the profile of drug-resistant TB obtained from Rumah Sakit Universitas Indonesia (RSUI) Depok period October 2024. Design of this study is a quantitative-descriptive where the data of patients obtained from the patients’ medical records in the period of October 2024. The findings of this study showed the total number of drug-resistant TB was 104 with 3 cases of HIV and 70 patients having Linezolid in their regimen. Most of the patients are male with mean of age 41.3 years. New cases and RR/MDR TB level are dominated while on the other hand there’s 9 cases of After Failure and 4 others are After Loss to Follow-up. Median values obtained for patients’ leukocytes, hemoglobin, and platelets are 7818.0, 11.9, 279.5 respectively.